Anomalous CO2 content in the Gallicano thermo-mineral spring (Serchio Valley, Italy) before the 21 June 2013, Alpi Apuane earthquake (M = 5.2). (2015) - Pierotti, L.; Botti, F.; D'Intinosante, V.; Facca, G.; Gherardi, F.
Highlights: Ongoing hydrogeochemical monitoring network since 2002 in Tuscany, Italy. Variations of deep originated geothermal fluids have been monitored. CO2 positive anomaly occurred as precursor of the 2013 seismic swarm. Abstract: Since late 2002, a continuous automatic monitoring network is operating in Tuscany, Central Italy, to investigate the geochemical response of selected aquifers to local seismic activity. The monitoring is aimed at identifying possible earthquake geochemical precursors. The network is currently constituted by six stations, all equipped with sensors for the measurement of temperature, pH, redox potential, electrical conductivity, CO2 and CH4 dissolved concentration, that have been installed in the areas of highest seismic risk of the region. By combining geochemical data gathered from the automatic station of Gallicano (Garfagnana, Northern Tuscany), and obtained via chemical analyses of spring water samples collected during periodic field surveys in the area surrounding this station, the most significant aspects of the deep fluid circulation paths feeding the Gallicano thermo-mineral system have been investigated, and the geochemical baseline of the Gallicano spring defined. The CO2 continuous signal recorded by the Gallicano automatic station has been then processed over the period 2003–2013 in the search for anomalies possibly related to local seismic activity. A substantial anomaly in CO2 content has been observed at Gallicano in conjunction with the Alpi Apuane earthquake ( M = 5.2) of 21 June 2013.